A comparative study between nasal clips and anterior nasal packing in septoplasty/submucosal resection patients at VIMS Bellary, Karnataka - Kurle, Geeta; Patil V., Shruthi; N., Manjunath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Nasal packing is used primarily to control bleeding, for internal stabilization and to prevent postoperative complications in endonasal surgeries. Nasal septal clip is one of the alternatives, whose effectiveness in surgical practice is less studied upon. To compare the effectiveness between nasal septal clip and anterior nasal packing following septoplasty/submucous resection. Methods: Prospective Randomised Controlled Study was conducted in Department of Otolaryngology at Vijayanagara Institution of Medical Sciences, Bellary, between November 2014 to May 2016. Study involved 100 patients fulfilling inclusion and exclusion criteria. Adopting sealed envelope technique, patients were allotted into two equal groups for anterior nasal pack and nasal septal clip following septoplasty or submucosal resection. Interventions were done following standard procedures and data was collected by using pre-tested proforma. Results: Mean age of anterior nasal pack group and nasal septal clip group was 27.86 and 25.24 years respectively. Intra-operatively, packing with nasal septal clip was easier with significantly less trauma to mucous membrane (X2= 6.353, P= 0.011), consuming significantly less time (t= 9.329, P<0.0001) and support provided to septum could be assessed visually when compared to anterior nasal packing. During immediate post-operative period and while pack removal, nasal septal clip had significantly less complications (P < 0.001). Follow-up complications like septal haematoma, synaechiae & septal perforations were lesser in nasal septal clip group Conclusions: During intra-operative period, immediate post-operative period, during nasal pack removal and during follow-up period nasal septal clip provided technical superiority, smooth post-operative experience and lesser complications compared to anterior nasal packing proving nasal septal clip to be a better choice for nasal packing. Limitations of NSC are its availability and cost.